Persepsi Mahasiswa Jurusan Hukum dalam Penggunaan AI untuk Menerjemahkan Dokumen Legal: Peluang dan Tantangan - Umul Fajar Khoiriah; Aninda Shinta Fatimatus Siha; Putri Hanifah Rahmani; Anam Sutopo; Dwi Haryanti (Samudra Publisher, 2024)
In this era, AI has influenced into all aspects of life, even in the world of translation. In this research, the researchers are interested in investigating law students' perceptions related to AI in legal document translation. This research is important because the use of AI in the translation of legal documents can speed up the translation process. This study examines the benefits of using AI in legal document translation according to law students and challenges in using AI in legal document translation according to law students. This study uses a qualitative study method, by conducting interviews with 2 law students. The data was analyzed using thematic method of analysis. In this study, the findings is law students perceive AI as a beneficial tool for translating legal documents due to its efficiency and accessibility, but emphasize the necessity of human review to ensure contextual accuracy and adherence to legal standards. For future research, it is recommended to add different fields of legal documents and be more specific in examining the AI applications used.